The Edge of the Earth. Climate Change in Photography and Video. - Ramade, Bénédicte; Demos, T.J.; Roth, Paul
Aubé, Jean-Pierre ; Aquin, Benoit ; Baier, Nicolas ; Balkin, Amy ; Berrada, Hicham ; Boisjoly, Raymond ; Burtynsky, Edward ; Charrière, Julian ; Goin, Peter ; Hatakeyama, Naoya ; Hayeur, Isabelle ; Henner, Mishka ; Jordan, Chris ; Mendel, Gideon ; Merolla, Brandi ; Misrach, Richard ; Missika, Adrien ; Pivi, Paola ; Rauchenberg, Robert ; Richer, Evariste ; Rutkausas, Andreas ; Sternfeld, Joel ; Stewart, Sharon ; Walde, Paul
Klimaatverandering, anthropocene, milieu, landschap
Catalogus naar aanleiding van de tentoonstellingthe Edge of the Earth: Climate Change in photography and Video, Ryerson Image center, Toronto, 14 september tot 4 december 2016.
boek
Keywords: T.J. Demos